Fear of campaign violence and support for democracy and autocracy. (September 2022) - von Borzyskowski, Inken; Daxecker, Ursula; Kuhn, Patrick M.
Election violence is common in many developing countries and has potentially detrimental implications for democratic consolidation. Drawing on political psychology, we argue that citizens' fear of campaign violence undermines support for democracy while increasing support for autocracy. Using individual-level survey data from 21 electoral democracies in Sub-Saharan Africa, we find robust support for our argument. Citizens fearing campaign violence are less likely to support democracy and multi-party competition, more likely to favor a return to autocracy, and less likely to turn out to vote. Our findings have important implications for democratic survival and provide further impetus for reducing electoral violence.